Genomic structure of human polyoma virus JC: nucleotide sequence of the region containing replication origin and small-T-antigen gene. - Miyamura, T (1983)
The nucleotide sequence of the region of human polyoma virus JC DNA between 0.5 and 0.7 map units from a unique EcoRI cleavage site was determined and compared with those of the corresponding regions of another human polyoma virus, BK, and simian virus 40 DNAs. Within this region consisting of 945 base pairs, we located the origin of DNA replication near 0.7 map units, the entire coding region for small T antigen, and the splice junctions for large-T-antigen mRNA. The deduced amino acid sequences for small T antigen and the part of large T antigen markedly resembled those of polyoma virus BK and simian virus 40. The results strongly suggest that polyoma virus JC has the same organization of early genome as polyoma virus BK and simian virus 40 on the physical map, with the EcoRI site as a reference point.